A high-sulfur petroleum coke-based sulfur self-doped mesoporous carbon supported Fe-TM bimetallic alloy catalyst and its preparation method and application
Through the use of high-sulfur petroleum coke-based sulfur self-doped mesoporous carbon-loaded Fe-TM bimetal alloy catalyst, the problem of resource utilization of high-sulfur petroleum coke-sulfur and the challenge of improving the performance of magnesium-based hydrogen storage materials has been solved, and low-cost and efficient catalytic effects and environmental protection advantages have been achieved.
Patent Information
- Application Number
- CN202510065190.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2045-01-16
AI Technical Summary
It is difficult for high-sulfur petroleum coke to effectively utilize its sulfur resources, and traditional activation methods have problems of equipment corrosion and high cost. At the same time, magnesium-based solid hydrogen storage materials face challenges such as high operating temperature and slow kinetics in applications.
High sulfur petroleum coke sulfur self-doped mesoporous carbon-supported Fe-TM bimetallic alloy catalyst is used. This catalyst is formed by activation of potassium ferrate and reducing calcination under a hydrogen atmosphere, avoiding the use of traditional activators, promoting the stable fixation of sulfur elements and the formation of Fe-TM alloys.
It significantly reduces the peak dehydrogenation temperature of magnesium-based materials, improves catalytic performance, avoids equipment corrosion and high costs, and makes full use of the sulfur resources in high-sulfur petroleum coke, which has environmental protection and economic advantages.
Smart Images

Figure CN119524882B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of solid waste resource utilization and hydrogen storage catalysis technology, and in particular to a high-sulfur petroleum coke-based sulfur self-doped mesoporous carbon-supported Fe-TM bimetallic alloy catalyst, and a preparation method and application thereof. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] At present, hydrogen storage technologies can be divided into three main types: high-pressure gas, low-temperature liquid, and metal hydride solid. Although the first two technologies perform well under specific conditions, they are limited by efficiency, cost or safety issues and are difficult to meet future human needs for energy use in different scenarios. Metal hydride hydrogen storage, especially magnesium-based solid hydrogen storage material magnesium hydride (MgH2), has attracted widespread attention in the field of solid-state hydrogen storage due to its advantages such as high hydrogen storage density (7.6wt.%), abundant resources and low cost. However, in practical applications, it faces challenges such as high operating temperature, large reaction enthalpy, and slow hydrogen absorption and desorption kinetics. Adding catalytic components is an effective strategy to improve the hydrogen storage performance of MgH2.
[0004] High-sulfur petroleum coke is an industrial by-product produced in the delayed coking process of the petroleum industry, with a bulk sulfur content greater than 3wt%. As the high-sulfur and heavy content of crude oil becomes increasingly serious, the total amount of high-sulfur petroleum coke produced by delayed coking has increased sharply. High-sulfur petroleum coke faces comprehensive restrictions and serious surplus problems from factory ex-works, customs clearance to combustion. Its high-value disposal or recycling has become a problem that needs to be solved urgently.
[0005] At present, it is disclosed that high-sulfur petroleum coke is activated by strong alkali or strong acid (KOH, NaOH or H3PO4, etc.) to generate activated carbon. However, the use of these activators will cause severe corrosion of the equipment and a large amount of washing water. In addition, under strong chemical reaction conditions, the bulk sulfur in high-sulfur petroleum coke is easily unstable and released, and the sulfur resource potential contained in it is not fully utilized. Carbon materials loaded with metals can be used as catalysts to improve the hydrogen storage performance of magnesium-based materials. At the same time, non-metallic sulfur atoms doped with carbon materials can induce the redistribution of atomic charge density to further improve their catalytic ability. Therefore, developing a green and economical high-sulfur petroleum coke functionalization strategy and applying it to the catalytic modification of the hydrogen storage performance of magnesium-based materials can open up a new path for the high-quality synergistic conversion of carbon and sulfur in high-sulfur petroleum coke. Summary of the invention
[0006] In order to overcome the above problems, the present invention provides a high-sulfur petroleum coke-based sulfur self-doped mesoporous carbon supported Fe-TM bimetallic alloy catalyst and a preparation method and application thereof.
[0007] In order to achieve the above technical objectives, the present invention adopts the following technical solutions:
[0008] The first aspect of the present invention provides a composition of a high-sulfur petroleum coke-based sulfur self-doped mesoporous carbon supported Fe-TM bimetallic alloy catalyst, comprising:
[0009] High sulfur petroleum coke, potassium ferrate and transition metal chloride salts;
[0010] Among them, the mass ratio of high-sulfur petroleum coke to potassium ferrate is 1: (0.5-2), and the molar ratio of transition metal chloride to potassium ferrate is 1: (0.8-1.2);
[0011] The sulfur content in high-sulfur petroleum coke is 3~10 wt%.
[0012] The second aspect of the present invention provides a high-sulfur petroleum coke-based sulfur self-doped mesoporous carbon supported Fe-TM bimetallic alloy catalyst, which is formed by ball milling the composition described in the first aspect, calcining under inert atmosphere protection, and reducing calcining under hydrogen atmosphere.
[0013] The third aspect of the present invention provides a method for preparing the high-sulfur petroleum coke-based sulfur self-doped mesoporous carbon-supported Fe-TM bimetallic alloy catalyst according to the second aspect, comprising the following steps:
[0014] (1) ball milling high-sulfur petroleum coke, potassium ferrate and transition metal chloride to obtain a first intermediate;
[0015] (2) The first intermediate is heated to a set temperature at a set heating rate under the protection of an inert atmosphere to obtain a second intermediate;
[0016] (3) maintaining the temperature conditions set in step (2), switching the atmosphere to a hydrogen atmosphere, performing reduction calcination, cooling to room temperature after calcination, and washing to obtain the high-sulfur petroleum coke-based sulfur self-doped mesoporous carbon-supported Fe-TM bimetallic alloy catalyst.
[0017] The fourth aspect of the present invention provides the use of the high-sulfur petroleum coke-based sulfur self-doped mesoporous carbon supported Fe-TM bimetallic alloy catalyst described in the second aspect in catalyzing MgH2 dehydrogenation.
[0018] The beneficial effects of the present invention are:
[0019] (1) The present invention provides a high-sulfur petroleum coke-based sulfur self-doped mesoporous carbon-supported Fe-TM bimetallic alloy catalyst and its preparation method and application. The high-sulfur petroleum coke-based sulfur self-doped mesoporous carbon-supported Fe-TM bimetallic alloy catalyst provided by the present invention is a sulfur self-doped mesoporous carbon-supported Fe-TM solid solution alloy material formed by calcining high-sulfur petroleum coke under the activation of potassium ferrate in an inert atmosphere and reducing calcining in a hydrogen atmosphere.
[0020] (2) During the calcination process under the protection of an inert atmosphere, potassium ferrate replaces the traditional strong base or strong acid activator and plays a dual function of "activation-modification". Potassium ferrate forms alkaline activation products at high temperatures, introducing more active sites on the surface of the carbon framework formed by the carbonization of high-sulfur petroleum coke; at the same time, it effectively promotes the migration of sulfur from the inside of the petroleum coke to the surface of the carbon framework and stably fixes it on the carbon matrix; in addition, potassium ferrate introduces an Fe metal source, allowing the catalyst material to be modified with Fe metal. During the reduction calcination process under a hydrogen atmosphere, Fe and transition metals (TM) diffuse through solid crystals to form a solid solution alloy. During the reduction calcination process, the high-sulfur petroleum coke will be further carbonized and activated, promoting the migration of sulfur from the inside of the petroleum coke to the surface of the carbon framework and uniformly self-doping it into the carbon skeleton structure, ultimately forming a Fe-TM solid solution alloy material loaded with sulfur self-doped mesoporous carbon.
[0021] (3) The use of potassium ferrate as an activator for high-sulfur petroleum coke not only avoids equipment corrosion and large amounts of washing water consumption, but also introduces an Fe metal source, reduces the amount of additional metal precursors added, optimizes the process flow, reduces production costs, and significantly improves environmental benefits.
[0022] (4) In the present invention, high-temperature reduction is used to induce solid-state crystal diffusion alloying of the Fe-TM bimetallic, thereby avoiding the catalytic deactivation caused by spontaneous oxidation of nano-Fe, ensuring the catalytic activity of Fe, and further stimulating the synergistic catalytic effect of the bimetallic to improve the catalytic performance.
[0023] (5) The high-sulfur petroleum coke-based sulfur self-doped mesoporous carbon-loaded Fe-TM bimetallic alloy catalyst provided by the present invention can significantly reduce the peak dehydrogenation temperature of magnesium-based materials by 80~110 K. The catalytic effect is comparable to that of the catalyst prepared by the traditional route, but its cost-effectiveness and environmental advantages are significant, demonstrating the huge industrial application potential of high-sulfur petroleum coke in the field of hydrogen storage. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0025] Figure 1The preparation process of high-sulfur petroleum coke-based sulfur self-doped mesoporous carbon supported Fe-TM bimetallic alloy catalyst;
[0026] Figure 2 XPS measurement spectra of the high-sulfur petroleum coke-based sulfur self-doped mesoporous carbon-supported Fe-TM bimetallic alloy catalyst FeCu@SC prepared in Example 1 and the material prepared in Comparative Example 1;
[0027] Figure 3 The N2 adsorption / desorption isotherms and pore size distribution diagram of the high-sulfur petroleum coke-based sulfur self-doped mesoporous carbon supported Fe-TM bimetallic alloy catalyst FeCu@SC prepared in Example 1 and the material prepared in Comparative Example 1;
[0028] Figure 4 The XRD spectrum of the high-sulfur petroleum coke-based sulfur self-doped mesoporous carbon supported Fe-TM bimetallic alloy catalyst Fe-Ni@SC prepared in Example 4;
[0029] Figure 5 The XRD spectrum of the composite material FeO-Ni@SC prepared in Comparative Example 2;
[0030] Figure 6 This is the XRD spectrum of the sulfur self-doped mesoporous carbon supported Fe single metal catalyst Fe@SC prepared in Comparative Example 3;
[0031] Figure 7 This is the XRD spectrum of the composite material prepared in Comparative Example 4;
[0032] Figure 8 It is the peak dehydrogenation temperature of the high-sulfur petroleum coke-based sulfur self-doped mesoporous carbon-supported Fe-TM bimetallic alloy catalyst Fe-Ni@SC prepared in Example 4 for catalytic modification of magnesium-based hydrogen storage. DETAILED DESCRIPTION
[0033] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0034] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.
[0035] A first typical embodiment of the present invention provides a composition of a high-sulfur petroleum coke-based sulfur self-doped mesoporous carbon supported Fe-TM bimetallic alloy catalyst, comprising:
[0036] High sulfur petroleum coke, potassium ferrate and transition metal chloride salts;
[0037] Among them, the mass ratio of high-sulfur petroleum coke to potassium ferrate is 1: (0.5-2), and the molar ratio of transition metal chloride to potassium ferrate is 1: (0.8-1.2);
[0038] The sulfur content in high-sulfur petroleum coke is 3~10 wt%.
[0039] In one or more embodiments, the metal corresponding to the transition metal chloride salt is selected from one of chromium, manganese, cobalt, nickel, niobium or copper.
[0040] A second typical embodiment of the present invention provides a high-sulfur petroleum coke-based sulfur self-doped mesoporous carbon-supported Fe-TM bimetallic alloy catalyst, which is formed by ball milling the composition described in the first aspect, calcining under inert atmosphere protection, and reduction calcining under hydrogen atmosphere.
[0041] In one or more embodiments, the method of calcining under inert atmosphere protection includes: heating to a set temperature at a set heating rate under inert atmosphere protection.
[0042] Preferably, the set heating rate is 5-10 K / min; the set temperature is 973-1173 K.
[0043] In one or more embodiments, the method of reduction calcination under hydrogen atmosphere includes: maintaining the calcination temperature under the protection of an inert atmosphere, switching the atmosphere to a hydrogen atmosphere, and performing reduction calcination.
[0044] Preferably, the reduction calcination temperature is 973-1173 K, and the reduction calcination time is 2-4 h;
[0045] The volume fraction of H2 is 50~100 wt%, and the flow rate is 20~50 mL / min.
[0046] A third typical embodiment of the present invention provides a method for preparing the high-sulfur petroleum coke-based sulfur self-doped mesoporous carbon-supported Fe-TM bimetallic alloy catalyst according to the second aspect, comprising the following steps:
[0047] (1) ball milling high-sulfur petroleum coke, potassium ferrate and transition metal chloride to obtain a first intermediate;
[0048] (2) The first intermediate is heated to a set temperature at a set heating rate under the protection of an inert atmosphere to obtain a second intermediate;
[0049] (3) maintaining the temperature conditions set in step (2), switching the atmosphere to a hydrogen atmosphere, performing reduction calcination, cooling to room temperature after calcination, and washing to obtain the high-sulfur petroleum coke-based sulfur self-doped mesoporous carbon-supported Fe-TM bimetallic alloy catalyst.
[0050] In one or more embodiments, in step (1), during the ball milling process, the ball-to-material ratio is (20-50):1, the ball milling speed is 300-500 rpm, and the ball milling time is 6-10 h.
[0051] Ball milling is used to refine the powder particle size, shorten the diffusion path, and form a highly dispersed first intermediate.
[0052] In one or more embodiments, in step (2), the inert atmosphere is selected from nitrogen or argon.
[0053] In one or more embodiments, in step (2), the heating rate is set at 5-10 K / min; and the temperature is set at 973-1173 K.
[0054] In one or more embodiments, in step (3), the temperature of the reduction calcination under hydrogen atmosphere is the same as the temperature of the calcination under inert atmosphere protection in step (2); 973-1173 K, and the reduction calcination time is 2-4 h;
[0055] The volume fraction of H2 is 50~100 wt%, and the flow rate is 20~50 mL / min.
[0056] In one or more embodiments, in step (3), the washing method comprises:
[0057] Use high-purity deionized water for washing until the pH of the washed filtrate is 7±0.1, and no precipitation is produced when the washed filtrate is titrated with silver nitrate solution.
[0058] A fourth typical embodiment of the present invention provides the use of the high-sulfur petroleum coke-based sulfur self-doped mesoporous carbon-supported Fe-TM bimetallic alloy catalyst described in the second aspect in catalyzing MgH2 dehydrogenation.
[0059] In one or more embodiments, the mass ratio of the high-sulfur petroleum coke-based sulfur self-doped mesoporous carbon supported Fe-TM bimetallic alloy catalyst to MgH2 is (5~15): (95~85).
[0060] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.
[0061] Figure 1The preparation process of high-sulfur petroleum coke-based sulfur self-doped mesoporous carbon supported Fe-TM bimetallic alloy catalyst is shown in Figure 1 , synthesis of high-sulfur petroleum coke-based sulfur self-doped mesoporous carbon supported Fe-TM bimetallic alloy catalyst.
[0062] Example 1
[0063] Preparation of high-sulfur petroleum coke-based sulfur self-doped mesoporous carbon supported Fe-TM bimetallic alloy catalyst:
[0064] (1) Synthesis of the first intermediate:
[0065] Weigh 1 g of high-sulfur petroleum coke, 1 g of potassium ferrate and 0.68 g of cupric chloride and place them in a ball mill; add zirconium oxide balls at a ball-to-material ratio of 30:1, and use a planetary ball mill for mechanical high-energy ball milling for 8 h.
[0066] (2) Calcination under inert atmosphere protection:
[0067] The first intermediate was placed in a metal nickel boat and transferred to a horizontal tube furnace. Under the protection of an argon inert atmosphere, the temperature was increased to 1173 K at a heating rate of 5 K / min to obtain a second intermediate.
[0068] (3) Reduction calcination under hydrogen atmosphere:
[0069] The gas source was switched to hydrogen atmosphere with a flow rate of 30 mL / min and a volume fraction of 100 wt%; reduction calcination was performed at 1173 K for 2 h. During the reduction calcination process, Fe and transition metals diffused in solid crystals to form a solid solution alloy, and sulfur was uniformly self-doped into the carbon skeleton.
[0070] (4) Byproduct removal
[0071] The product obtained in step (3) is washed with high-purity deionized water until the pH of the filtrate is 7 and no white precipitate is generated when a silver nitrate solution is added dropwise. The washed product is placed in an 80°C forced air drying oven and dried for 24 h. After drying, it is ground to obtain a high-sulfur petroleum coke-based sulfur self-doped mesoporous carbon-supported Fe-TM bimetallic alloy catalyst FeCu@SC.
[0072] Comparative Example 1
[0073] The difference between this comparative example and Example 1 is that potassium ferrate is not added in step (1), and the other schemes are the same as Example 1.
[0074] Figure 2 The XPS measurement spectra of the high-sulfur petroleum coke-based sulfur self-doped mesoporous carbon supported Fe-TM bimetallic alloy catalyst FeCu@SC prepared in Example 1 and the material prepared in Comparative Example 1 are shown in FIG. Figure 2 It can be seen that the high-sulfur petroleum coke-based sulfur self-doped mesoporous carbon-loaded Fe-TM bimetallic alloy catalyst FeCu@SC prepared in Example 1 clearly confirms the presence of Cu, Fe, O, C and S elements, the ratio of Cu and Fe atoms is close to 1:1, and the surface S content reaches 2.76%, indicating that the sulfur element has successfully achieved self-doping in the carbon framework. The XPS spectrum of the material prepared in Comparative Example 1 shows that the metal source failed to achieve effective loading, and the surface sulfur content was significantly reduced to only 1.06%. Potassium ferrate, as a strong oxidant, can significantly activate the carbon matrix, introduce more active sites on the surface of the carbon framework, effectively promote the migration of sulfur from the inside of the petroleum coke to the surface of the carbon framework, and stably fix it on the carbon matrix. On the contrary, without the addition of potassium ferrate, the carbon matrix lacks sufficient active sites, and its inert structure cannot effectively promote the migration and binding of sulfur elements, further limiting the self-doping of sulfur.
[0075] Figure 3 The N2 adsorption / desorption isotherms and pore size distribution of the high-sulfur petroleum coke-based sulfur self-doped mesoporous carbon supported Fe-TM bimetallic alloy catalyst FeCu@SC prepared in Example 1 and the material prepared in Comparative Example 1 are shown in FIG. Figure 3 It can be seen that the high-sulfur petroleum coke-based sulfur self-doped mesoporous carbon supported Fe-TM bimetallic alloy catalyst FeCu@SC prepared in Example 1 exhibits a IV isotherm with a BET specific surface area of 370.2 m 2 / g, the average pore size of BJH desorption is 4.9 nm, which is a mesoporous structure; in contrast, in Comparative Example 1 where potassium ferrate is not added, the material still maintains a dense structure and fails to effectively form pores.
[0076] Example 2
[0077] The difference between this embodiment and embodiment 1 is that the raw material 0.68 g of copper chloride in step (1) is replaced by 1.36 g of niobium chloride, and the other schemes are the same as those in embodiment 1, thereby obtaining a high-sulfur petroleum coke-based sulfur self-doped mesoporous carbon-supported Fe-TM bimetallic alloy catalyst FeNb@SC.
[0078] Example 3
[0079] Preparation of high-sulfur petroleum coke-based sulfur self-doped mesoporous carbon supported Fe-TM bimetallic alloy catalyst:
[0080] (1) Synthesis of the first intermediate:
[0081] Weigh 1 g of high-sulfur petroleum coke, 1 g of potassium ferrate and 0.66 g of cobalt chloride and place them in a ball mill; add zirconium oxide balls at a ball-to-material ratio of 30:1, and use a planetary ball mill for mechanical high-energy ball milling for 8 h.
[0082] (2) Calcination under inert atmosphere protection:
[0083] The first intermediate was placed in a metal nickel boat and transferred to a horizontal tube furnace, and heated to 1073 K at a heating rate of 5 K / min under the protection of an argon inert atmosphere.
[0084] (3) Reduction calcination under hydrogen atmosphere:
[0085] The gas source was switched to hydrogen atmosphere with a flow rate of 30 mL / min and a volume fraction of 100 wt%; reduction calcination was performed at 1073 K for 2 h. During the reduction calcination process, Fe and transition metals diffused in solid crystals to form a solid solution alloy, and sulfur was uniformly self-doped into the carbon skeleton.
[0086] (4) Byproduct removal
[0087] The product obtained in step (3) is washed with high-purity deionized water until the pH of the filtrate is 7 and no white precipitate is generated when a silver nitrate solution is added dropwise. The washed product is placed in an 80°C forced air drying oven and dried for 24 h. After drying, it is ground to obtain a high-sulfur petroleum coke-based sulfur self-doped mesoporous carbon-supported Fe-TM bimetallic alloy catalyst FeCo@SC.
[0088] Example 4
[0089] The difference between this embodiment and embodiment 3 is that the raw material 0.66 g of cobalt chloride in step (1) is replaced by 0.65 g of nickel chloride, and the other schemes are the same as those in embodiment 3, thereby obtaining a high-sulfur petroleum coke-based sulfur self-doped mesoporous carbon-supported Fe-TM bimetallic alloy catalyst Fe-Ni@SC.
[0090] Figure 4 This is the XRD spectrum of the high-sulfur petroleum coke-based sulfur self-doped mesoporous carbon supported Fe-TM bimetallic alloy catalyst Fe-Ni@SC prepared in Example 4. Strong diffraction peaks corresponding to the FeNi solid solution alloy were observed at three positions of 2θ=43.5°, 50.9° and 74.9°, corresponding to the (111), (200) and (220) crystal planes, respectively, indicating that a highly crystallized alloy structure was generated.
[0091] Comparative Example 2
[0092] The difference between this comparative example and Example 4 is that “weigh 1 g of high-sulfur petroleum coke, 1 g of potassium ferrate and 0.65 g of nickel chloride, and place in a ball mill” is replaced by “weigh 1 g of high-sulfur petroleum coke, 1 g of potassium ferrate and 0.65 g of nickel chloride, and place in a mortar”; “add zirconium oxide balls at a ball-to-material ratio of 30:1, use a planetary ball mill for mechanical high-energy ball milling, and the ball milling time is 8 h” is replaced by “grind thoroughly in a mortar to mix the reaction precursors evenly”, and other schemes are the same as Example 4.
[0093] Comparative Example 3
[0094] The difference between this comparative example and Example 4 is that nickel chloride is not added in step (1), and the other schemes are the same as Example 4.
[0095] Comparative Example 4
[0096] The difference between this comparative example and Example 4 is that the process of reduction calcination in hydrogen atmosphere in step (3) is replaced by "continue to maintain argon atmosphere, do not switch to hydrogen atmosphere, flow rate is 30 mL / min, volume fraction is 100 wt%", and the other schemes are the same as Example 4.
[0097] Figure 5 The XRD spectrum of the composite material FeO-Ni@SC prepared in Comparative Example 2 shows that the diffraction peak intensities of the FeNi alloy at 2θ=43.5°, 50.9° and 74.9° are Figure 4 At the same time, characteristic diffraction peaks corresponding to Fe3O4 were tested at five positions of 2θ=17.3°, 30.0°, 35.3°, 57.2° and 62.6°, which means that the comparative example 2 did not adopt high-energy mechanical ball milling treatment, resulting in insufficient uniformity of the precursor mixture, limiting the alloying reaction of Fe and Ni under high temperature conditions. Fe and Ni failed to fully form a uniform solid solution alloy, but were partially oxidized to generate Fe3O4 phase, which further proved that high-energy mechanical ball milling plays an important role in the synthesis of bimetallic alloy catalysts.
[0098] Figure 6 This is the XRD spectrum of the sulfur self-doped mesoporous carbon supported Fe single metal catalyst Fe@SC prepared in Comparative Example 3. Figure 6 All the diffraction peaks presented in the results correspond to Fe3O4, and the catalytic activity of Fe3O4 for MgH2 is extremely poor. This indicates that without the participation of the second transition metal, the nano-iron formed by the iron source of potassium ferrate is deactivated by spontaneous oxidation in the air and cannot play a catalytic role in subsequent applications.
[0099] Figure 7This is the XRD spectrum of the composite material prepared in Comparative Example 4. It can be observed from the figure that in addition to the diffraction peaks corresponding to the FeNi solid solution alloy, a small amount of Fe3O4 diffraction peaks also appear. This shows that hydrogen is a necessary condition to promote the full formation of the bimetallic solid solution alloy.
[0100] The above results indicate that potassium ferrate plays multiple and critical roles in this preparation method. Its specific functions include activating pore expansion, providing iron source and realizing controllable sulfur self-doping. At the same time, high-energy ball milling, second transition metal source and hydrogen are necessary conditions for the full formation of sulfur self-doped mesoporous carbon-loaded Fe-TM bimetallic alloy catalysts.
[0101] Example 5
[0102] In this example, the high-sulfur petroleum coke-based sulfur self-doped mesoporous carbon supported Fe-TM bimetallic alloy catalyst Fe-Ni@SC prepared in Example 4 was used to catalyze MgH2 to prepare a MgH2 / FeNi@SC composite magnesium-based hydrogen storage material. The specific steps are as follows: 0.2 g FeNi@SC and 1.8 g MgH2 were weighed and placed in a stainless steel ball mill, 100 g zirconia ball milling balls were added according to a ball-to-material ratio of 50:1, and argon protective gas was filled into the stainless steel ball mill. The ball mill was milled in a planetary ball mill in a positive and negative rotation alternating manner for 6 h. To prevent the release of hydrogen caused by local high temperature, the ball milling was rested for 10 min every 30 min. After the ball milling was completed, the ball milling mixture was collected in a glove box, i.e., the MgH2 / FeNi@SC composite magnesium-based hydrogen storage material. The hydrogen release performance of MgH2 / FeNi@SC was measured by a synchronous thermogravimetric analyzer, and its peak dehydrogenation temperature was tested by heating from room temperature to 823 K at a heating rate of 5 K / min.
[0103] Figure 8 is the peak dehydrogenation temperature of the high-sulfur petroleum coke-based sulfur self-doped mesoporous carbon supported Fe-TM bimetallic alloy catalyst Fe-Ni@SC for catalytic modification of magnesium-based hydrogen storage prepared in Example 4, from Figure 8 It can be found that compared with the original MgH2, the dehydrogenation temperature is reduced by 105 K, showing excellent catalytic performance.
[0104] The above results show that the method of the present invention can be used to successfully prepare high-sulfur petroleum coke-based sulfur self-doped mesoporous carbon-supported Fe-TM bimetallic alloy catalysts. High-energy mechanical ball milling and high-temperature reduction treatment ensure the full alloying of the Fe-TM bimetal. Thanks to the synergistic catalytic effect of the Fe-TM bimetal and the regulating effect of self-doped sulfur on the electronic properties of the carbon matrix, efficient catalysis of magnesium-based hydrogen storage materials is achieved.
[0105] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A high-sulfur petroleum coke-based sulfur self-doped mesoporous carbon supported Fe-TM bimetallic alloy catalyst, characterized in that: The composition of the high-sulfur petroleum coke-based sulfur self-doped mesoporous carbon supported Fe-TM bimetallic alloy catalyst is formed by ball milling, calcining under nitrogen or argon atmosphere protection, and reduction calcining under hydrogen atmosphere; The composition comprises high-sulfur petroleum coke, potassium ferrate and transition metal chloride; the mass ratio of high-sulfur petroleum coke to potassium ferrate is 1:(0.5-2), and the molar ratio of transition metal chloride to potassium ferrate is 1:(0.8-1.2); the sulfur content in high-sulfur petroleum coke is 3-10 wt%; the metal corresponding to the transition metal chloride is selected from one of cobalt, nickel, niobium or copper; During the ball milling process, the ball-to-material ratio was (20-50):1, the ball milling speed was 300-500 rpm, and the ball milling time was 6-10 h; Under the protection of nitrogen or argon atmosphere, the temperature is raised to the set temperature at a set heating rate; the set heating rate is 5~10K / min; the set temperature is 973~1173 K; The method of reduction calcination under hydrogen atmosphere includes: maintaining the calcination temperature under the protection of nitrogen or argon atmosphere, switching the atmosphere to hydrogen atmosphere, and performing reduction calcination; the reduction calcination time is 2 to 4 hours; During the reduction calcination process in a hydrogen atmosphere, Fe and transition metal TM diffuse through solid crystals to form a solid solution alloy. During the reduction calcination process, the high-sulfur petroleum coke will be further carbonized and activated, promoting the migration of sulfur elements from the inside of the petroleum coke to the surface of the carbon framework and uniformly self-doping into the carbon skeleton structure.
2. The method for preparing the high-sulfur petroleum coke-based sulfur self-doped mesoporous carbon supported Fe-TM bimetallic alloy catalyst according to claim 1, characterized in that: The steps include: (1) ball milling high-sulfur petroleum coke, potassium ferrate and transition metal chloride to obtain a first intermediate; (2) The first intermediate is heated to a set temperature at a set heating rate under the protection of a nitrogen or argon atmosphere to obtain a second intermediate; (3) maintaining the temperature conditions set in step (2), switching the atmosphere to a hydrogen atmosphere, performing reduction calcination, cooling to room temperature after calcination, and washing to obtain the high-sulfur petroleum coke-based sulfur self-doped mesoporous carbon-supported Fe-TM bimetallic alloy catalyst; In step (1), during the ball milling process, the ball-to-material ratio is (20-50):1, the ball milling speed is 300-500 rpm, and the ball milling time is 6-10 h; In step (2), the heating rate is set at 5-10 K / min; the temperature is set at 973-1173 K; In step (3), the temperature of the reduction calcination under hydrogen atmosphere is the same as the temperature of the calcination under nitrogen or argon atmosphere protection in step (2), which is 973~1173 K; the reduction calcination time is 2~4 h.
3. The preparation method according to claim 2, characterized in that: The washing method includes: washing with high-purity deionized water until the pH of the washed filtrate is 7±0.1, and no precipitation is generated when the washed filtrate is titrated with a silver nitrate solution.
4. Use of the high-sulfur petroleum coke-based sulfur self-doped mesoporous carbon supported Fe-TM bimetallic alloy catalyst according to claim 1 in catalyzing MgH2 dehydrogenation.
5. The use according to claim 4, characterized in that The mass ratio of high-sulfur petroleum coke-based sulfur self-doped mesoporous carbon supported Fe-TM bimetallic alloy catalyst and MgH2 is (5~15): (95~85).
Citation Information
Patent Citations
Preparation method of novel coal-based porous carbon electrode material
CN114890420A
Potassium ferrate activated semi-coke, preparation method thereof and application of potassium ferrate activated semi-coke in catalyzing persulfate to degrade organic pollutants in water
CN117720942A
High-sulfur petroleum coke-based porous carbon-supported metal sulfide catalyst as well as preparation method and application thereof
CN118268005A